Ofatumumab added to dexamethasone in patients with relapsed or refractory chronic lymphocytic leukemia: Results from a phase II study - Doubek, Michael; Brychtova, Yvona; Panovska, Anna; Sebejova, Ludmila; Stehlikova, Olga; Chovancova, Jana; Malcikova, Jitka; Smardova, Jana; Plevova, Karla; Volfova, Pavlina; Trbusek, Martin; Mraz, Marek; et al. (American journal of hematology, 2015)
The treatment of relapsed/refractory chronic lymphocytic leukemia (CLL) remains a challenging clinical issue. An important treatment option is the use of high-dose corticosteroids. The purpose of this clinical trial was to determine the efficacy and toxicity of an ofatumumab-dexamethasone (O-Dex) combination in relapsed or refractory CLL. The trial was an open-label, multicenter, nonrandomized, Phase II study. The O-Dex regimen consisted of intravenous ofatumumab (Cycle 1: 300 mg on day 1, 2,000 mg on days 8, 15, and 22; Cycles 2-6: 1,000 mg on days 1, 8, 15, and 22) and oral dexamethasone (40 mg on days 1-4 and 15-18; Cycles 1-6). The O-Dex regimen was given until best response, or a maximum of six cycles. Thirty-three patients (pts) were recruited. Twenty-four (73%) pts completed at least three cycles of therapy. The remaining nine pts were prematurely discontinued owing to Grade 3/4 infections (seven pts), disease progression (one pt), or uncontrollable diabetes mellitus (one pt). Overall response rates/complete remissions (ORR/CR) were achieved in 22/5 pts (67/15%). The median progression-free survival (PFS) was 10 months. In pts with p53 defects (n = 8), ORR/CR were achieved in 5/2 pts (63/25%) with a median PFS of 10.5 months. The median overall survival (OS) was 34 months. The Grades 3-5 infectious toxicity in 33% of pts represented the most frequent side effect during the treatment period. In conclusion, the O-Dex regimen shows a relatively high ORR and CR with promising findings for PFS and OS. The study was registered at www.clinicaltrials.gov (NCT01310101).
Keywords: Tumor Suppressor Protein p53; Aged; Recurrence; lidé středního věku; senioři; recidiva; Antibodies, Monoclonal; Antineoplastic Agents; lidé; nádorový supresorový protein p53; Middle Aged; Female; Mutation; chronická lymfatická leukemie; rozvrh dávkování léků; mutace; Male; ženské pohlaví; Survival Analysis; Humans; mužské pohlaví; analýza přežití; Leukemia, Lymphocytic, Chronic, B-Cell; Drug Administration Schedule; Drug Therapy, Combination; protinádorové látky; kombinovaná farmakoterapie; dexamethason; monoklonální protilátky; Dexamethasone